Miksi itämerensuomessa on prepositioita? - Grünthal, Riho (Virittäjä, 2005)
Why do the Finnic languages have prepositions? (englanti) 1/2005 (109) Why do the Finnic languages have prepositions? The article studies the development of prepositional phrases in the Finnic languages. Comparing the Finnic languages with other Finno-Ugrian languages it is evident that the occurence of prepositional phrases in the Finnic languages cannot be explained as the result of a single change but as the result of long-term language development. The most significant of the differences between the adpositional phrases of the various Finno-Ugrian languages is the word order of the adposition and its complement. All the Finno-Ugrian languages have postpositions, but the Saami and the Finnic languages also feature prepositions. Many of the prepositions have a different meaning and are often more abstract than the postpositions. Furthermore, the complement of the prepositional phrases is most often in the partitive case, whereas that of the postpositional phrases is in the genitive. In all the Finnic languages, however, there are considerably fewer prepositions than postpositions. Besides there being exclusively prenominal and exclusively postnominal adpositions, the Finnic languages also have bipositional adpositions, which can appear either as pre- or postpositions. Nevertheless, the number of prepositions does not exceed more than 20-25% of all adpositions. The writer analyses the morphosyntactic background of Finnic prepositions and prepositional phrases in terms of historical linguistics and language typology. Besides prepositions being a rare category in the Finno-Ugrian languages, the Finnic languages are also among the relatively few languages in the world that feature both pre- and postpositions. In terms of language typology, the unusual nature and word order of the adpositional phrases are connected with word order typology and implicational universals. The Finnic languages can, in principle, be counted among those that follow the SVO basic word order. These are often prepositional, though not as typically so as the postpositional SOV languages. The SOV word order is considered older and more typical of the Finno-Ugrian languages, and to have been the original basic word order in the Finnic languages, too. This is one of the reasons why the Finnic languages still have a lot more postpositions than prepositions. The development of the prevailing mixed system can be attributed to two main factors: language-internal changes and language contact. Regarding diachronic development, the postpositions are considered to be older than the prepositions. However, many factors have influenced the adoption of the preposition category and the prepositional phrase, such as changes in word order, case marking of nominal constituents and use of the partitive, although these have had an indirect rather than a direct effect on the use of prepositions. The influence of foreign languages on the system of adpositions has been very limited, not least because of their fixed morphosyntactic structure. The Finnic languages therefore have very few adpositions loaned from other languages. Changes in the adposition system are instead dependent on the morphological and syntactic structure of the language. Thus the principal mechanisms of change that led to the adoption of the preposition category were changes in word order and in the grammatical relations of adverbs, and, though considerably less common, borrowing. The oldest prepositional phrase type is the Finnish structure of the type ennen jotakin before something. The roots of this appear to be in the Finno-Ugrian way of expressing time relations using a separative case. Use of a separative case is one of the most common means of expressing comparison in both Finno-Ugrian and the worlds languages in general. This kind of comparison may indeed represent one of the earliest morphosyntactic preconditions for the use of prepositional phrases in the Finnic languages. Riho Grnthal